MINIMIZATION OF WATER NEEDS IN IRAQI AGRICULTURE IN LIGHT OF THE PREVAILING CROPPING COMBINATION DURING - Assad A. Abdullah,; Zuhal R. Kadhim, (IRAQI JOURNAL OF AGRICULTURAL SCIENCES, 2023)
The research aims to study the optimal allocation of irrigation water that is used to irrigate various agricultural crops at the level of Iraq. In order to achieve the goal of the research, two economic models were formulated according to the linear programming technique. The first model aimed to minimize the water needs of the prevailing crop combination during the average period (2017-2020), while the second model aimed to maximize the total profit margin of the water unit for the crop combination that minimizes the water needs during the same period. The first model was estimated with two proposed plans. The first proposed plan included non-imposing legislative restrictions related to the allocation of certain areas for basic agricultural crops that bias the food security requirements of the population, as well as crops that were recently banned from import by the Iraqi government, while the proposed second plan included the imposition and addition of restrictions of legislative areas that did not appear in the table of the optimal solution for the first plan. Results indicated that there is a surplus of water resource for the proposed economic plans according to the two estimated models, its quantity amounted to about 363.361, 9.178 million m3 for each plan, respectively, compared to the total amount of irrigation water needed for the current cropping combination, which was estimated at about 4.736726 billion m3 during the average mentioned period. Results of the analysis of the two estimated models also showed a preference for the results of plans with legislative restrictions as a result of the expansion in the cultivation of most basic and important crops and vegetables for local consumption.